2000
DOI: 10.3168/jds.s0022-0302(00)74993-9
|View full text |Cite
|
Sign up to set email alerts
|

Crop Processing and Chop Length of Corn Silage: Effects on Intake, Digestion, and Milk Production by Dairy Cows

Abstract: Effects of corn silage crop processing and chop length on intake, digestion, and milk production were evaluated. Corn silage treatments were harvested at one-half milkline stage of maturity (65% whole-plant moisture content) and at 0.95-cm theoretical length of cut without processing (control) or 0.95-, 1.45-, or 1.90-cm theoretical length of cut with processing at a 1-mm roll clearance. Twenty-four multiparous Holstein cows averaging 71 d in milk at trial initiation were in a replicated 4 x 4 Latin square des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
159
3
9

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(204 citation statements)
references
References 18 publications
24
159
3
9
Order By: Relevance
“…This result was similar to previous study (Kononoff and Heinrichs, 2003) which suggested increasing the proportion of particles >19.0 mm may be a primary factor affecting chewing activity of dairy cattle. In the current study, reducing lucerne hay particle size did not signifi cantly affect total ruminating time, but signifi cantly reduced eating time, which was different from other reports (Bal and Shaver, 2000;Schwab and Shaver, 2002), it was possibly due to the greater differences of lucerne hay length. Present diets had the same sources and amount of NDF, and ingredients were same among different treatments.…”
Section: Discussioncontrasting
confidence: 99%
“…This result was similar to previous study (Kononoff and Heinrichs, 2003) which suggested increasing the proportion of particles >19.0 mm may be a primary factor affecting chewing activity of dairy cattle. In the current study, reducing lucerne hay particle size did not signifi cantly affect total ruminating time, but signifi cantly reduced eating time, which was different from other reports (Bal and Shaver, 2000;Schwab and Shaver, 2002), it was possibly due to the greater differences of lucerne hay length. Present diets had the same sources and amount of NDF, and ingredients were same among different treatments.…”
Section: Discussioncontrasting
confidence: 99%
“…A quantity of 10 ml of residual ruminal fluid was immediately used to determine pH by using a pH meter (PP-201; GOnDO Electronic, Taipei, Taiwan), 10 ml were kept for NH 3 -N analysis (Bal et al, 2000) and another 10 ml were preserved for VFA determination by adding 1 ml of 25% metaphosphoric acid. Samples were frozen (−20°C) for later analysis.…”
Section: Samplesmentioning
confidence: 99%
“…Positive effects on DMI with reduced particle size have been reported in some studies (Weigand et al, 1993;Stockdale and Beavis, 1994) but have not been observed in others (Schwab et al, 2002). In contrast, total-tract NDF digestibility has been observed to increase with increasing chop length (Bal et al, 2000), and as a result, interactive effects between fiber digestion and chop length may exist.…”
Section: Introductionmentioning
confidence: 95%